THE INFLUENCE OF TA’LIM MUTA’ALIM UNDERSTANDING TO THE DEVELOPMENT OF SANTRI CHARACTER (Research on Nurussalam Islamic Boarding School Medangasem Jayakerta Karawang) - Khalid Ramdhani; Laila Ngindana Zulfa (TAWASUT, 2020)
Ta’lim Muta’alim is a classic book written by Syekh Al Zarnuzi on 593 H. As the writer of Ta'lim al-Muta'allim Thariq al-Ta'allum, he emphasizes the aspect of character values physical and spiritual. In this book, education is not only transfer of knowledge and skills, but the most important here is the transfer of character values. The purpose of writing this article is to examine the influence of Talim Muta’alim understanding to santri character development. The research methodology used in this research is based on quantitative approach with path analysis model that explores causality (causal effectual), which analyzes the relationship between Ta’lim Muta’alim understanding variable and santri character at Nurussalam Islamic Modern Boarding School Medangasem Jayakerta Karawang. The results showed that Ta’lim Muta’alim understanding positively and significantly 20,3% influence the santri’s character which suported all of member of boarding school, especially kyai, teachers and santri can run the teaching-learning process. Keyword : Education, Ta’lim Muta’alim, Santri Character.